Representation of the views of individual authorities and pressure groups on PPSMI in Malaysian English newspapers / Amjad Raji bin Jusoh - Amjad Raji, Jusoh (2012)
This study is aimed at analysing the discursive construction ofcontroversy about the medium of instruction (MOI) for schoolsin the news media discourse in Malaysia. The data were collected from two mainstream English newspapers, The Star and The New Straits Times (January 2009 – June 2010). In Malaysia, national schools at the primary and secondary levels; and vernacular (Chinese and Tamil) schools at the primary level use English, instead of the national language, Bahasa Malaysia (BM), to teach Mathematics and Science, upon a directive issued by the Education Ministry in 2003. The policy is popularly known as PPSMI (PengajarandanPembelajaranSainsdanMatematikDalamBahasaInggeris, tr., Teaching of Mathematics and Science in English). However, in 2009, the Ministry decided to reverse the PPSMI policy and revert to BMas the medium of instruction. The reversal of the policy was discussed widely including in the space of the media. This study looked into how the English print media, specially, the two mainstream newspapers, The Star and The New Straits Time, covered the issue through the genres of news reports, editorials and opinion editorials. More specifically, the study aimed at analysing how different individuals and pressure groups in the country co-constructed and negotiated the issue as their voices were mediated by the columns of the editorials or news reporters. The analysis involved an exploration of the contents, linguistic means of realization (i.e., description of linguistic items and interpretation of the linguistic items), and an analysis of the stances based on the discourse-historical approach (DHA)constructed by Reisigl and Wodak(2001),Wodak et al. (2001), Wodak (2009) within the paradigm of critical discourse analysis (CDA) which involved national language, culture, constitution and education in Malaysia. The analysis shows that the authors of the texts used ‘selective’ mention of individuals and authorities, which ultimately facilitated a particular reading of the texts.